Productivity and Allocative Efficiency of Quail (Cortunix Coturnix Japonica) Production using Different Rearing Techniques in Nigeria. - Oladimeji, Y. U.; Yusuf, H. O.; Yusuf, H. A.; Shuaibu, H.; Olarewaju, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Small scale poultry production plays a major role in bridging the protein deficit and sustain rural livelihood in Nigeria. This study assesses the productivity and allocative efficiency (AE) of quail (Cortunix coturnix japonica) production using different rearing techniques in Nigeria. In this study, both primary and secondary data were collected from 193 quail poultry farmers comprising of 78 battery cage system (BCS) and 115 deep litter system (DLS) operators using a multi-stage random sampling procedure. Descriptive statistics, profitability indices and stochastic frontier function were used to analyse the data. The stochastic frontier cost function was used to estimate the factors influencing AE of farmers in quail production. The results show a gross margin of N1, 455.51, net poultry returns of N1157.47 per quail bird for BCS thrives better compared to N800.00 and N751.96 estimated in DLS respectively. The estimated profit margin (26.81 %) and return on investment (1.37) in BCS were also higher than 26.54 % and 1.36 respectively in DLS. The ROI result indicates that a N1.00 investment in BCS and DLS yields N0.37 and N0.36 respectively. AE results revealed that the coefficient of costs of feed (0.287), hired labour (-0281), family labour (0.309) and depreciation of fixed items (-005) were found to be statistically significant variables in BCS quail production. Conversely, costs of feed (0.109), cost of hired labour (-0.007) and family labour (0.188) statistically influence DLS quail production. The inefficiency sources model for BCS showed that age, formal education, access to credit and investment are the significant factors. Furthermore, formal education, access to production credit and level of investment contributed significantly to the explanation of efficiency in DLS production unit. Therefore, it is suggested that quail farmers should strive to optimize efficient use of inputs to increase output and profit. This will be an impetus to achieving sustainable poultry production in the studied areas.